Implementation of Islamic Spiritual Guidance in Reducing Anxiety for Prenatal Patients at Muhammadiyah Metro General Hospital - Hardiansyah, Fadhil; Helwa, Aulia; Rahmayanty, Dinny; Zubaidah, Zubaidah (Alfuad: Jurnal Sosial Keagamaan, 2024)
Anxiety describes a person's emotional feelings that arise when facing an event or occurrence in his life. The anxiety experienced by pregnant women as prenatal patients is motivated by lack of knowledge and inexperience about the labor process, physical conditions that do not support suddenly, lack of emotional support from family and environment, inappropriate delivery schedule, or pain when contractions occur become one of the backgrounds of anxiety in prenatal patients. So, to reduce anxiety in prenatal patients, help from third parties is needed to provide a sense of calm through psychological assistance in the form of motivation. Muhammadiyah Metro General Hospital, is a hospital that provides these services through Islamic spiritual guidance services for each patient. So, the purpose of this study is to describe the Implementation of Islamic Spiritual Guidance in reducing anxiety for prenatal patients at Muhammadiyah Metro General Hospital. This research uses a type of field research with qualitative descriptive methods. Researchers directly carry out data collection and information related to the research location. Data collection techniques used by the author are interviews, observations and documentation using source triangulation and triangulation techniques to test the validity of research data. The results of this study stated that there were prenatal patients who experienced anxiety such as Reality or objective Anxiety, Neurotic Anxiety, and Moral Anxiety. Islamic Spiritual Guidance in reducing anxiety in prenatal patients at Muhammadiyah Metro General Hospital is implemented by providing psychological, spiritual and fiqh pain assistance and education to prenatal patients.